Site preference and defect engineering of a highly efficient blue-emitting phosphor Sr2SiO4:Ce3+/K+ toward thermally enhanced luminescence. Issue 8 (17th March 2023) - Zhao, Kai; Ma, Zhihong; Yin, Li; Hui, Bin; Si, Han; Tong, Xinlin; Tang, Huidong; Cao, Peng; Huang, Saifang
Abstract : The aliovalent doping of Ce 3+ /K + in α′-Sr2 SiO4 leads to a thermally enhanced phosphor with bright blue emission, and electron traps modulated by defect engineering contribute to an abnormal thermal quenching phenomenon. Abstract : The blue-emitting phosphor is one of the trichromatic phosphors essential for the development of near-ultraviolet (nUV) pumped phosphor-converted white light-emitting diodes (pc-WLEDs). Efficiency and thermal stability are two critical factors for the potential application of phosphors in solid-state lighting. In this work, we report a highly efficient blue-emitting phosphor, α-Sr2 SiO4 :0.02Ce 3+ /0.02K + (emission peak at 425 nm) with superior thermally enhanced photoluminescence properties. The Rietveld refinement results suggest that Ce 3+ preferentially occupies the nine-fold coordinated Sr2 site only whereas K + occupies both Sr1 and Sr2 sites in the host structure. Its emission intensity gradually increases with increasing temperature and retains 120% of its room-temperature peak intensity at 250 °C. Besides, its luminescence spectral peak does not shift at elevated temperatures. Under nUV irradiation, the phosphor is highly luminous with an excellent internal quantum efficiency (IQE) of 91.7%. The abnormal thermal quenching phenomenon can be ascribed to the defect energy levels introduced by defect engineering using an aliovalent doping strategy of Ce 3+ and K + in the α-Sr2 SiO4 host structure. The as-fabricated WLED prototypes demonstrated the great potential of the highly efficient blue-emitting phosphor with superior thermal stability for solid-state lighting applications.